Evolution of Two Short Interspersed Elements in Callorhinchus milii (Chondrichthyes, Holocephali) and Related Elements in Sharks and the Coelacanth. (13th May 2017) - Luchetti, Andrea; Plazzi, Federico; Mantovani, Barbara
Abstract: Short interspersed elements (SINEs) are non-autonomous retrotransposons. Although they usually show fast evolutionary rates, in some instances highly conserved domains (HCDs) have been observed in elements with otherwise divergent sequences and from distantly related species. Here, we document the life history of two HCD-SINE families in the elephant shark Callorhinchus milii, one specific to the holocephalan lineage (CmiSINEs) and another one (SacSINE1-CM) with homologous elements in sharks and the coelacanth (SacSINE1s, LmeSINE1s). The analyses of their relationships indicated that these elements share the same 3′-tail, which would have allowed both elements to rise to high copy number by exploiting the C. milii L2-2_CM long interspersed element (LINE) enzymes. Molecular clock analysis on SINE activity in C. milii genome evidenced two replication bursts occurring right after two major events in the holocephalan evolution: the end-Permian mass extinction and the radiation of modern Holocephali. Accordingly, the same analysis on the coelacanth homologous elements, LmeSINE1, identified a replication wave close to the split age of the two extant Latimeria species. The genomic distribution of the studied SINEs pointed out contrasting results: some elements were preferentially sorted out from gene regions, but accumulated in flanking regions, while others appear more conserved within genes. Moreover, data from the C. milii transcriptome suggest that these SINEs could be involved in miRNA biogenesis and may be targets for miRNA-based regulation.